Motives in Online Shopping through Digital Platforms in Textile: Risk Perception and Purchase Intention - TURHAN, GÜLDEN (My University, 2022)
This study aims to provide a great deal of insight into how risk perception and purchase intention differ for the consumer with different online shopping motives. Data were collected through a questionnaire with 359 voluntary consumers aged 18-28 living in Istanbul. 14 motives leading them to online shopping through digital platforms for textile products were defined with the focus group technique. First, clustering analysis was conducted to define consumers according to the guiding motives in online shopping. Next, whether the consumer segments identified by these motives have different levels of risk perception and purchase intention was investigated via ANOVA analysis.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Pazarlama; Tekstil Mühendisliği ve Teknolojisi; Tekstil İşletmeciliği ve Yönetimi; Mühendislik ve Teknoloji; Social Sciences and Humanities; Management; Marketing; Textile Engineering and Technology; Textile Management; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Malzeme Bilimi; Ekonomi ve İş; MALZEME BİLİMİ, TEKSTİL; İŞLETME; YÖNETİM; Engineering, Computing & Technology (ENG); Social Sciences (SOC); MATERIALS SCIENCE; ECONOMICS & BUSINESS; MATERIALS SCIENCE, TEXTILES; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; online shopping motives; digital platforms; textile; risk perception; purchase intention